Pure Leydig cell tumor of the ovary: a rare presentation of a rare entity in a pregnant patient - Anwar Rjoop; Alia Almohtaseb; Daoud O Al Aruri; Dina Hyari; Mohammad Abu shugaer (Future Science OA, 2024)
Aim: Leydig cell tumors (LCT) are rare neoplasms that represent less than 0.1% of all ovarian tumors. This tumor usually presents with signs and symptoms of excess androgen levels. Diagnosis is made based on a combination of history, laboratory findings, imaging techniques and histopathological findings.Case: We present the case of a 35-year-old gravida five para 3+1 pregnant woman with a unilateral ovarian cystic mass that was discovered incidentally during a cesarean section. The cyst measured 9 cm in its maximum dimension. A left oophorectomy was performed after the delivery of an alive male baby. Morphological and immunophenotypic findings were consistent with those of a pure Leydig cell tumor.Conclusion: Leydig cell tumors are uncommon and usually present with hyperandrogenism. The presentation could be polymorphic, ranging from the rapid onset of virilization to being asymptomatic.